An Association Between Critical Macroeconomic Indicators and Economic Growth: A Study of United Arab Emirates - Shefali Saini (UIN Mataram, 2021)
Introduction- Macroeconomic variables such as Gross capital formation, Final consumption expenditure, Merchandise exports play a vital role in the economic performance of any country. Purpose- The study analyses the association between Gross capital formation, Final consumption expenditure, Merchandise exports and GDP (current US) of UAE Research Methodology- For the purpose of the research study critical Macroeconomic variables such as Gross capital formation, Final consumption expenditure, Merchandise exports have been identified to check for their magnitude of impression on GDP (current US) of UAE. Yearly secondary data from the period of 2001 to 2019 (21st century) has been taken into consideration and it has been passed through descriptive analysis, the paper also employed linear regression to establish that there exists a fairly strong positive correlation. Findings- There has been a significant relationship between the identified variables indicated by p value, f value, t stat and showcase a positive high degree of correlation.